STUDY OF WAR TRAUMA THROUGH THE PRISM OF GENRE FEATURES OF OLEKSANDR MYKHED’S WORK "CALL SIGN FOR YOVA" - Haikova, Anna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The purpose of the study is to analyze the genre-compositional and ideological-stylistic features of the work of Oleksandr Mykhed “Сall sign for Yova”, the role of micro-images in the creation of a specific genre synthesis. Research methodology. The methodology of “trauma studio” was used to study the problem. Research results. Oleksandr Mykhed’s book “Сall sign for Yova” is a kind of martyrology, in which the author tries to record the war crimes of the occupiers, using a combination of documentary and artistic forms for this. Three sections of the narrative – objective, subjective and philosophical – combine a chronicle of events and a narrative of fixation, “photographic” with a deeply personal, reflective and experiential experience. The specificity of the genre and composition of this work is the use of elements of reportage, chronicle, memoirs, interviews – a kind of collage of intermittent memories, “overlaying” texts with different time layers. At the same time, it is a successful attempt to “write trauma” – to narrate the pain and shock of the experience, so the work seems to “balance” on the border of fiction and documentary literature. Here, two genre dominants are clearly traced – the diary and the chronicle. The experience of a traumatic experience affects the composition of the work both as a whole and in the composition of individual essays, even the composition of micro images. Mykhed’s style is characterized by the antithetical modeling of a phrase, in which oxymoron is embedded. The antithesis in the work also becomes one of the central compositional techniques that form the bipolarity of the book’s artistic world. The book gains its depth thanks to the structure that allows it to speak not only in the author’s voice, but also in four key dialogues (Voices of War), representing different dimensions of experience.